High-Intensity Focused Ultrasound Ablation of Prostate Cancer: 15 Years of Follow-up - V. A. Solovov; A. A. Tiurin (Креативная хирургия и онкология, 2023)
Introduction. Prostate cancer (PC) is considered to be one of the most common malignancies in men. In recent years, conventional PC treatments have been supplemented with highly effective minimally invasive therapies such as highintensity focused ultrasound ablation (HIFU). Only a few studies have been published on the long-term oncological effectiveness of HIFU therapy for prostate cancer. Aim. To evaluate the oncological efficacy of HIFU in the treatment of prostate cancer in a long-term follow-up. Materials and methods. The retrospective analysis included the treatment outcomes of 171 patients with prostate cancer who underwent HIFU therapy at the Samara Clinical Oncology Dispensary in 2007–2009. The mean age of the patients was 69.7 years. Of these, 48 had a low risk of progression according to D’Amico, 57 patients — intermediate risk and 66 — high risk of progression. The follow-up period comprised 13–15 years (median 14.3 years). Positive histological findings, elevated PSA and/or the appearance of local or distant metastases were interpreted as recurrence. The Kaplan-Meier method was used to graphically represent survival curves. A multiparameter Cox proportional hazards regression analysis was performed to assess the prognostic significance of various clinical data in overall, cancer-specific and recurrence-free survival. All values of p<0.05 were considered statistically significant. Results and discussion. The overall fifteen-year survival for patients in the low-risk, intermediate-risk, and high-risk groups accounted for 52.1, 56.1, and 37.9%, respectively. Fifteen-year PC-specific survival was determined in 90.1% of patients. Fifteen-year recurrence-free survival for patients in the low-risk, intermediate-risk, and high-risk groups comprised 95.4, 80.7 and 69.7%, respectively. A significant risk factor for recurrence was the distribution according to the D’Amico progression risk scale. Conclusion. HIFU therapy demonstrated good long-term oncologic results in the treatment of patients with prostate cancer.